Trophic State of The Lubuk Siam Lake, Siak Hulu Sub-disctrict, Kampar District Based on Trophic Index (TRIX) - Yohana Nelly Destina Siboro; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract             There are several human activitiessuch as agriculture and palm plantation are conducted around the Lubuk Siam Lake and thus the remains of fertilizer may enter to the water and affects trophic state in general. To understand the trophic state of the Lubuk Siam Lake’s watersbased on Vollenweider’s Trophic Index (TRIX), a research was conducted in February - March 2017.There were 3 sampling stations namely Station 1 (inlet area), Station 2 (the middle of the lake), and Station 3 (outlet area). In each station there were 3 sampling points, in the surface (50 cm), 2 Secchi depth (126 cm) and 3 Secchi depth (189cm). Sampling were conducted 3 times, once/week. Water quality parameters measured were DIN (Dissolved Inorganic Nitrogen), total phosphorus, dissolved oxygen, chlorophyll-a, transparency, temperature and pH.Results shown that the transparency was 63 – 89 cm, temperature 28.5 – 30.530C, pH 6.83 – 7.27, total phosphorus 0.02 – 0.08 mg/L, DIN  0.45 – 0.73 mg/L, chlorophyll-a12.76 – 44.86 mg/m3, oxygen saturation 52.78%– 103.29%. The TRIX value indicates that the Lubuk Siam Lake can be categorized as mesotrophic to hypereutrophic. Keywords : Water quality, Trophic state, Lubuk Siam Lake, TRIX